Mechanisms, Pathways and Characteristics of Carbon Sinks Related toSoil and Water Conservation from Perspective of Carbon Peak and Carbon Neutralization - Li Zhiguang; Wang Haiyan; Wang Junxiong (Shuitu baochi tongbao)
[Objective] The main mechanisms, pathways and characteristics of carbon sinks related to soil and water conservation were explored from the perspective of carbon peak, carbon neutralization goals, and the schedule of Chinese national strategy objectives and goals in order to provide references for comprehensively improving the capacity of soil and water conservation to sequester carbon, and to scientifically promote the high-quality development of comprehensive control of soil and water losses. [Methods] Based on various soil and water conservation measures and their synergistic mechanisms, and referring to relevant research results from home and abroad, the discipline application basis, basic mechanisms, three main pathways, and four kinds of material performance of soil and water conservation related to carbon sinks were systematically discussed and analyzed. Additionally, the main characteristics of soil and water conservation related to carbon sinks were identified. [Results] The role of soil and water conservation related to carbon sinks comes from the joint participation of three types of soil and water conservation measures: plant measures, engineering measures, and farming measures through a variety of pathways that include plants, soil, and water. These measures can reduce CO2 in the atmosphere and convert it into a variety of carbon compounds for storage in plants and their products, in soil, and in water. The carbon sink pathways related to soil and water conservation include the plant pathway, the soil pathway, and the water pathway. Carbon sinks related to soil and water conservation include biomass, inanimate organic matter, soil organic matter, and water carbon. The main characteristics of soil and water conservation that affect carbon sinks include the joint action of a variety of control measures, the interweaving of a variety of carbon sink pathways, and the locality of carbon sink materials. The characteristics of carbon sinks are obvious over short time periods, and weak carbon sinks are clear over yearly cycles. [Conclusion] Soil and water conservation during this new period of ecological civilization construction should comprehensively promote soil and water conservation as a means of sequestering carbon, implement the monitoring and evaluation of carbon sinks, expand soil and water conservation measures that result in high carbon sinks, construct clean ecological small watersheds, avoid carbon emissions caused by soil erosion and damage control measures, further improve increment in carbon sinks, and consolidate the capacity of carbon sinks.